The humanization of childbirth as a tool in the fight against obstetric violence - Bomfim, Vitoria Vilas Boas da Silva (2022)
The objective is to assess whether the humanization of childbirth is effective in combating obstetric violence. This is an integrative literature review carried out through the Scientific Electronic Library Online (SciELO), Latin American and Caribbean Literature on Health Sciences (LILACS), Nursing Database (BDENF) and Medical Literature Analysis. and Retrieval System Online (MEDLINE), through the following Health Science Descriptors (DeCS): Bone Marrow Transplantation” and “Acute Myeloid Leukemia”. As inclusion criteria: articles available online, in full, in Portuguese, Spanish and English, that addressed the theme, in the last five years (2017-2022). As exclusion criteria: articles that did not cover the topic and repeated studies in the databases. From the initial search with the descriptors and Boolean operator defined, 254 studies were found in the selected base and after applying the inclusion and exclusion criteria, 33 studies were selected to compose the review. Professionals are less and less fascinated with providing individualized care, helping with rapid and medicalized delivery, using the excuse that there are few beds in the unit, or that there are many women ready to give birth, and therefore justify their excesses in unnecessary interventions, physical and psychological abuse.